Effect of Ramadan intermittent fasting on cognitive, physical and biochemical responses to strenuous short-term exercises in elite young female handball players - Graja, A.; Ghattassi, K.; Boudhina, N.; Bouzid, M. A.; Chahed, H.; Ferchichi, S.; Drisse, T.; Souissi, N.; Hammouda, O. (Physiology & Behavior, 2021)
The present study aimed to assess the effect of Ramadan intermittent fasting (RF) on cognitive and physical performance and biochemical responses to specific exercises in elite young female handball players. Twelve athletes participated in three experimental sessions: one week before Ramadan (BR), during the first week of Ramadan (FWR) and during the last week of Ramadan (LWR). The present crossover study was carried out in Tunisia during the 2013 Ramadan month lasting from 9 July to 7 august. During each session, a battery of tests was performed as follow: Hooper index, vigilance test (VT), Epworth sleepiness scale (ESS), five jump test (5-JT), modified agility T-test (MAT), maximal standing ball-throw velocity test (MSBVT) and Running-based Anaerobic Sprint (RAST) Test. Rating of perceived exertion (RPE) was recorded immediately after the RAST. Blood samples were collected before and after exercises during each session. The results showed that ESS scores were higher during LWR than BR (p < 0.05). Moreover, MSBVT time decreased (p < 0.05) during LWR, therefore performance enhanced. The power of three final sprints from the RAST decreased significantly only during LWR compared to BR (p < 0.05). RAST fatigue index and RPE scores were higher during LWR more than BR (p < 0.05). The results showed also that hematological measures (i.e., red blood cells, hemoglobin and hematocrit), plasma osmolarity and energetic markers were unaffected by RF. Biomarkers of muscle damage were higher after the RAST only during LWR compared to BR (p < 0.01 for all). In conclusion, RF increased ESS and decreased RAST performances associated with higher muscle damage and fatigue, especially at LWR. These previous alterations could be attributed to disturbances of sleep and circadian rhythms rather than nutritional deficiency or dehydratation.